1993
DOI: 10.1073/pnas.90.5.2050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential models for imprinted and nonimprinted components of human chromosome 15q11-q13 syndromes by fine-structure homology mapping in the mouse.

Abstract: Prader-Wil and Angelman syndromes are complex neurobehavioral contiguous gene syndromes whose expression depends on the unmasking of genomic imprinting for different genetic loci in human chromosome 15q11-q13. The homologous chromosomal region in the mouse genome has been fine-mapped by using interspecific (Mus spretus) crosses and overlapping, radiation-induced deletions to evaluate potential animal models for both imprinted and nonimprinted components of these syndromes. Four evolutionarily conserved sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…48 Initially, GABRB3 was proposed as an AS candidate gene, 49 but it was then excluded because a subtle microdeletion not encompassing the 50 and because of its biallelic expression in mouse brain. 51 Recently, targeted disruption of GABRB3 has been performed and homozygous mutant mice exhibit epilepsy, EEG abnormalities, and a phenotypic behaviour similar to AS. 52 Hence, the role of these genes in the AS phenotype cannot be definitively excluded but remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…48 Initially, GABRB3 was proposed as an AS candidate gene, 49 but it was then excluded because a subtle microdeletion not encompassing the 50 and because of its biallelic expression in mouse brain. 51 Recently, targeted disruption of GABRB3 has been performed and homozygous mutant mice exhibit epilepsy, EEG abnormalities, and a phenotypic behaviour similar to AS. 52 Hence, the role of these genes in the AS phenotype cannot be definitively excluded but remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotyping protocols used in such strategies can range from simple to complex and can be narrowly or broadly focused, with the output of any experiment dependent largely on the discriminating power of the phenotyping used. The extensive homologies between the genomes of mouse and human make it feasible to use the mouse for discovery of new mutations and phenotypes that aid in the functional annotation of the corresponding human DNA sequence and transcription maps.The region of mouse chromosome (Chr) 7 surrounding the pink-eyed dilution (p) locus that shares homology with human genomic regions 15q11-q13 and 11p14-p15 is being characterized by both genetic and molecular approaches (15,(19)(20)(21)(22)(23)(24)(25)(26). We previously reported initial results of a hemizygosity-screen strategy for recovering ENU-induced recessive mutations within the 4-to 5-cM Del(ru2 p) 46DFiOD deletion (15); this strategy is similar to a mutation-recovery experiment carried out for a 6-to 11-cM deletion at the more distally mapping Chr 7 tyrosinase [Tyr; previously, albino (c)] locus (14,16).…”
mentioning
confidence: 99%
“…The region of mouse chromosome (Chr) 7 surrounding the pink-eyed dilution (p) locus that shares homology with human genomic regions 15q11-q13 and 11p14-p15 is being characterized by both genetic and molecular approaches (15,(19)(20)(21)(22)(23)(24)(25)(26). We previously reported initial results of a hemizygosity-screen strategy for recovering ENU-induced recessive mutations within the 4-to 5-cM Del(ru2 p) 46DFiOD deletion (15); this strategy is similar to a mutation-recovery experiment carried out for a 6-to 11-cM deletion at the more distally mapping Chr 7 tyrosinase [Tyr; previously, albino (c)] locus (14,16).…”
mentioning
confidence: 99%
“…Multiple studies have shown an association of 15q11-13 markers to autism, and GABA A receptor genes have been identified as strong candidates to explain the occurrence of seizures in 30-35% of autistic patients (Buxbaum et al, 2002;Martin et al, 2000;Menold et al, 2001;Ma et al, 2005). The 15q11-13 locus contains a cluster of imprinted genes, expressed exclusively from one parental chromosome, as well as a cluster of three GABA A receptor subunit genes that are biallelically expressed (Nicholls et al, 1993). The 15q11-13 GABA A receptor genes are implicated in AS, as patients with a 15q11-13 deletion have a more severe phenotype, particularly in occurrence of seizures, than do individuals with UBE3A point mutations .…”
Section: Epigenetic Influences On Autism Risk: a Role For Gaba A mentioning
confidence: 99%